2014
DOI: 10.1027/1864-1105/a000109
|View full text |Cite
|
Sign up to set email alerts
|

Active and Sedentary Video Game Time

Abstract: This study used survey methodology to measure opinions of 13- to 15-year-olds (N = 176) about sedentary and active video games and the relative amount of time spent with those games, and evaluated correlations between time spent with those two types of games and the body mass index (BMI) of the respondent. Results showed no evidence of any correlation between BMI and relative time devoted to video game usage by type of game (active versus sedentary), nor any support for a correspondence between overall levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…26 Finally, the different studies involved participants from various countries or regions of the world (see table 2), as six studies (50%) were conducted in Europe, 27-29 32 33 36 five (42%) in North America 25 26 30 34 35 and one (8%) in South America. 31 Finally, seven studies (58%) had a large number of participants (more than 500), 25 27 28 30-33 two had an intermediate number of participants (100-499) 34 35 and three had a low number of participants (less than 100). 26 29 36…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Finally, the different studies involved participants from various countries or regions of the world (see table 2), as six studies (50%) were conducted in Europe, 27-29 32 33 36 five (42%) in North America 25 26 30 34 35 and one (8%) in South America. 31 Finally, seven studies (58%) had a large number of participants (more than 500), 25 27 28 30-33 two had an intermediate number of participants (100-499) 34 35 and three had a low number of participants (less than 100). 26 29 36…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Five studies investigated BMI, 25 29 30 33 35 three of them having a low risk of bias. Two low risk of bias studies 29 30 conducted in teenagers and adult populations found a moderate association between gaming and BMI, one low risk of bias study 33 found a weak association between gaming and BMI, while one low risk of bias study 35 found no association in teenagers. Based on these studies and because of the heterogeneity of studied populations, we conclude that there is preliminary evidence that increasing hours of video game playing is associated with increased BMI in adults only.…”
Section: Bmimentioning
confidence: 99%
See 2 more Smart Citations
“…);还会影响玩家的身体健康,如造成幻听,手腕疼痛,颈部疼痛,腕 部综合征,影响睡眠,导致肥胖 (Scharrer & Zeller, 2014;Turel, Romashkin, & Morrison, 2016;Williams, Yee, & Caplan, 2008;Wolfe et al, 2014 …”
Section: 引言unclassified